Trender i modernt franskt-judiskt tänkande - Lundgren, Svante (Nordisk judaistik, 2000)
The Jewish community in today’s France is the biggest in Europe and the third biggest in the world (next to the USA and Israel) with more than 600 000 members. The French Jews were the first in Europe to be emancipated and they showed strong assimilationistic tendencies, but during the second half of the 20th century, they developed a strong and proud Jewish identity. The Jewish community is, however, deeply divided: mainly into secular Jews and into religious Jews who are moving in the direction of a stricter Orthodoxy. The towering figure in modern French-Jewish thinking is Emmanuel Lévinas, the well-known Lithuanian-born philosopher. Among his disciples one can find such secular Jews as Alain Finkielkraut and such Ultra-Orthodox ones as the former Maoist Benny Lévy. The most important thinker within the centrist modern Orthodox position is Shmuel Trigano, a prolific Sephardic Jew born in Algeria. The Holocaust and the creation of the state of Israel have raised the question of the French tradition of reducing religion into a private thing. Many defend the French republican model with a secular state granting freedom of religion to individuals, while other look for a more communitarian and collective way of expressing Jewishness in France. This debate between "republicans" and "contrarevolutionairies" was particularly heated on the occasion of the bicentennary of the French revolution in 1989.